Analysis of energy resource production levels and existing reserves in Uzbekistan - Kaxramon R. Allayev; Ikromjon U. Rakhmonov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2025)
Relevance: the article highlights key trends in the extraction and processing of oil and gas resources in Uzbekistan. It analyzes the production volumes of oil, gas condensate, and natural gas, as well as the impact of technological and economic factors on industry development. Special attention is given to the issue of declining hydrocarbon production, the need for infrastructure modernization, and attracting investments. Goal: to assess the current state of Uzbekistan’s oil and gas sector and propose strategies for its sustainable development through modernization, investment attraction, and technological advancements. Methods: statistical analysis of oil and gas production volumes, evaluation of economic and technological factors affecting the industry, and review of international cooperation in the energy sector. Results: the research substantiates the need for deep gas processing and the development of the gas chemical industry to enhance energy security. The study also emphasizes the importance of international cooperation and the transit of energy resources through Kazakhstan. Additionally, the article highlights the necessity of implementing market mechanisms, improving energy efficiency, and diversifying the energy balance by increasing the share of renewable energy sources.